(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article focuses on the distinctive features of Uzbek dialectology, specifically the role of Bukhara dialect and its importance in enriching Uzbek language dialect corpora. It analyzes the phonetic, lexical, and grammatical characteristics of Bukhara dialect and highlights how it differs from other Uzbek dialects. The article also discusses the use of Bukhara dialect in linguistics, the changes in dialectal units, and the challenges of their scientific analysis. This research will aid in a deeper understanding of the dialectal features of the Uzbek language and the significance of Bukhara dialect in linguistic studies.